Integrated STEM through Project Based Learning and Guided Inquiry on Scientific Literacy Abilities in Terms of Self-Efficacy Levels - Hana Lestari; Ima Rahmawati (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThe research aims to describe and find out the different effects between project based learning models and integrated guided inquiry models with STEM (science, technology, engineering, and mathematics) on students' scientific literacy abilities in terms of self-efficacy levels. The study was conducted at Cibatok 1 Elementary School. The subject of this study is with 52 students of fifth grade . The research method was a quasi-experiment method with the-factorial 3x2 design. Two classes were given treatment, class V-A was given a project based model treatment, while class V-C was given a guided inquiry model treatment. The instruments used consisted of a questionnaire level of self-efficacy and a test of scientific literacy abilities. for measuring validity and reliability. Data analysis was performed with the two-way Anova test. Based on the results of the study, it was found that: (1) there was no difference in the influence of project based learning learning models and guided inquiry on the ability of scientific literacy; (2) there are differences in the ability of scientific literacy among students in high, medium and low levels of self-efficacy; (3) the scientific literacy ability of students with high levels of self-efficacy is better than middle and low levels of self-efficacy; (4) there is an effect of the interaction of learning models with the level of self-efficacy to learn together on students' scientific literacy abilities. The findings of this study are expected to be of practical use for teachers to develop aspects of self-efficacy and students' scientific literacy abilities.Keywords: learning models, scientific literacy ability, self-efficacy, STEM.Â AbstrakPenelitian ini bertujuan untuk mengetahui perbedaan pengaruh pembelajaran dengan model berbasis proyek dan model inkuiri terbimbing terintegrasi STEM (sains, teknologi, teknik, dan matematika) terhadap kemampuan literasi sains siswa ditinjau dari tingkat efikasi diri. Penelitian ini dilaksanakan di Sekolah Dasar Negeri Cibatok 1, dengan subjek penelitian siswa kelas V yang berjumlah 52 orang. Penelitian ini menggunakan metode quasi eksperimen dengan desain faktorial 3X2. Terdapat dua kelas yang diberikan perlakuan, kelas V-A diberikan perlakuan model berbasis proyek, sedangkan kelas V-C diberi perlakuan model inkuiri terbimbing. Instrumen yang digunakan terdiri dari angket tingkat efikasi diri dan tes kemampuan literasi sains, instrumen tersebut telah melalui uji validitas dan reliabilitas. Analisis data dilakukan dengan uji Anova dua jalur. Berdasarkan hasil penelitian, ditemukan bahwa: (1) tidak terdapat perbedaan pengaruh model pembelajaran project based learning dan Inkuiri terbimbing terhadap kemampuan literasi sains; (2) terdapat perbedaan kemampuan literasi sains antara siswa dengan tingkat efikasi diri tinggi, sedang dan rendah; (3) kemampuan literasi sains siswa yang tingkat efikasi diri tinggi lebih baik dari tingkat efikasi diri sedang dan rendah; (4) terdapat pengaruh interaksi model pembelajaran dengan tingkat efikasi diri secara bersama-sama terhadap kemampuan literasi sains siswa. Temuan penelitian ini diharapkan dapat digunakan secara praktis bagi guru untuk mengembangkan aspek self-efficacy dan kemampuan literasi sains siswa.Kata kunci: model pembelajaran, kemampuan literasi sains, efikasi diri, STEM.